Association of Three Polymorphisms rs11614913, rs2910146, and rs3746444 in miRNA-196a2, miRNA-146a, and miRNA-499 with Inflammatory Bowel Disease: A Systematic Review and Meta-Analysis - Ying Liu; Lingxin Xiong; Yan Zhou; Bingzhen Zheng; Tongjun Liu; Wei Xie (Gastroenterology Research and Practice)
Background. It has been found that single-nucleotide polymorphisms (SNPs) of microRNA might be involved in the development of inflammatory bowel diseases (IBDs). However, the related retrospective research has not been reported. In this work, we performed a meta-analysis to derive a more precise estimation of the associated relationship. Methods. We searched the studies on the association of SNPs of microRNA with the hereditary susceptibility of IBD in PubMed and Embase; eligible research was selected by screening the abstract and full text. The meta-analysis was performed based on the statistical software Stata 14.0, and besides, the odds ratio and 95% confidence interval were calculated to evaluate the strength of the association. Results. 159 papers were acquired from the PubMed and Embase databases, and five eligible articles containing nine case-control studies were selected. In the study, we first found that the association between miRNA-196a2 rs11614913 and IBD was insignificant. Then, the susceptibility of miRNA-146a rs2910146 to IBD increased significantly in allelic comparison, homozygote model, heterozygote model, and dominant model. Moreover, a positive relationship between miRNA-499 rs3746444 and IBD was identified in the homozygote model. Conclusion. Our findings demonstrated that miRNA-146a rs2910146 (G>C) polymorphism was associated with the susceptibility to IBD and miRNA-196a2 rs11614913 (T>C) and miRNA-499 rs3746444 (A>G) did not reveal an obvious relationship with the IBD susceptibility.